Pengaruh Penggunaan Cotton Bud terhadap Penyakit Peradangan Telinga (OTITIS) di Indonesia - Ainun Tiyas Affifah; Amelia Ambarwati; Revalina Mulsa Amelia Putri; Yunita Dini Pratika Sari; Liss Dyah Dewi A (STIKes Ibnu Sina Ajibarang, 2024)
Chronic suppurative otitis media (CSOM) can have a significant impact on hearing function. Recurrent middle ear infections and inflammation can damage the eardrum, hearing bones, and other auditory structures. Depending on the severity of the infection and response to treatment, temporary or permanent hearing loss may occur. People often use tools such as cotton swabs to clean the ears. The use of cotton buds can damage the ear canal. Repeated trauma can cause the ears to become inflamed. One of the symptoms of ear infections is watery ears. The purpose of this study was to determine the relationship between the frequency and frequency of using ear swabs with symptoms of watery ears. This study is an analytical observational study with a cross-sectional approach using the Fisher chi-square exact test. The target audience of this study is students, the survey was conducted using an online Google Form, And the technique used is purposive sampling. The results of this study revealed that the study participants amounted to 245 respondents. The age group of cotton bud users is the most 20 years old (36%). Of the 245 respondents who met the inclusion criteria, 96 respondents. The frequency of using cotton buds is the most < 4 times a week (91.7%). The highest number of cotton buds used < 5 cotton buds per ear toilet (88.5%). Conclusion of the study there was a significant relationship between the frequency of cotton bud use and watery ear complaints (P value = 0.43). There was no relationship between the amount of cotton bud use and watery ear complaints (P value = 0.43).